DEVELOPMENT OF THE EDUCATIONAL INSTRUMENT SKILLS OF THE UNDERGRADUATE STUDENT ON THE EDUCATIONAL CURRICULUM BY USING THE PROJECT-BASED LEARNING FOR SUPPORTING STUDENT’S SKILLS IN THE 21ST CENTURY - Khumyoo, Thip; Wongthitikun, Akkrawat; Phaudjantuk, Somyot (Journal of Educational Review Faculty of Education in MCU, 2021)
The purposes of this research article were 1) to investigate the effectiveness of the Project-Based Learning Lesson Plan (PJBLLP) in the educational learning measurement and evaluation subject, 2) to develop the instrument skills of the undergraduate students in the Bachelor of Education Program in Early Childhood Education by using the PJBLLP that supported students in the 21st Century skills between before and after instruction, and 3) to study the student’s satisfaction toward instruction by using the PJBLLP that supported students in the 21st Century skills. Samples were the undergraduate students in the Bachelor of Education Program in Early Childhood Education at Suan Dusit University that registered in the educational learning measurement and evaluation course among 30 students. Research instruments were 1) the PJBLLP plan, 2) the achievement test of the development of the instrument skills, 3) the evaluation form of the student’s satisfaction of the undergraduate students. Mean, standard deviation, and t-test were employed. The results showed that: 1) The effectiveness of the PJBLLP in the educational learning measurement and evaluation course was high and meet the standard criteria at level of 83.43/84.67. 2) The development of the instrument skills of the undergraduate students in the Bachelor of Education Program in Early Childhood Education using the PJBLLP that supported students in the 21st Century skills was shown that after the instruction by using the Project-Based learning was higher than before instruction significantly of 0.01. 3) The student’s satisfaction toward instruction by using the PJBLLP that supported students in the 21st Century skills by using the PJBLLP was very high especially in the PJBLLP 2, 4, 8 and 9.